Revisiting the wetland wise use concept after 50 years – ‘flogging a dead horse’ or ‘‘dusting the golden vase’ - Ritesh Kumar; C. Max Finlayson; Suchita Awasthi (Wetlands, 2026)
Introduced in the text of the Ramsar Convention on Wetlands over five decades ago, the wetland wise use concept was a unique recognition of human-nature connectedness and a genuine precursor to sustainable development. Yet, the use of the term has been inconsistent within the Convention, and its application has been limited by a curtailed outlining of principles and the implementation framework. An overtly ecological framing of the wetland wise use concept, as was framed in the early days of the Convention, is insufficient to guide conservation practices in addressing the contemporary challenges facing these ecosystems, as decisions regarding wise use are not solely scientific or ecological. A fit-for-purpose interpretation of wise use would unshackle the concept from an overly instrumental framing to one conveying a deeper human-nature connectedness, built around the diverse values of nature, and fostering forms of human-nature connectedness that value sustainability and enhance supporting behaviors. Wetlands need to be considered as complex social-ecological systems, with ‘wetland character’ as the ‘system identity’. Wetland wise use, rather than an end in itself, is best considered as a ‘form of environmental management’ which ensures the goal of ‘maintaining wetland character’, within a safe operating space. A desirable wise use process is one that recognizes plural worldviews and values of nature, builds on diverse knowledge systems, and uses a coproduction process to engage diverse stakeholders and the public towards the goal of maintaining wetland character.

Effective intensities of conservation management and ecological threats in improving ecosystem services synergies and mitigating its trade-offs - Weiwei Liu; Lijuan Cui; Rumiao Wang; Manyin Zhang; Wei Li; Wenjing Bo; Miaomiao Zhang; C. Max Finlayson (Journal of Geographical Sciences, 2026)

A Classification System for Colombian Wetlands: an Essential Step Forward in Open Environmental Policy-Making - Luisa Fernanda Ricaurte; Jorge E. Patiño; Diego Fernando Restrepo Zambrano; Juan Carlos Arias-G; Oscar Acevedo; Cesar Aponte; Ruth Medina; Mauricio González; Sergio Rojas; Carlos Flórez; Lina M. Estupinan-Suarez; Úrsula Jaramillo; et al. (Wetlands, 2019)

Are we adapting to climate change? A catchment-based adaptation assessment tool for freshwater ecosystems - Anna Lukasiewicz; Jamie Pittock; C. Max Finlayson (Climatic Change, 2016)

Institutional challenges of adopting ecosystem-based adaptation to climate change - Anna Lukasiewicz; Jamie Pittock; Max Finlayson (Regional Environmental Change, 2016)

Climate change and the wise use of wetlands: information from Australian wetlands - C. Max Finlayson (Hydrobiologia, 2013)

Preface: Climate change and wetlands in Australia - C. Max Finlayson (Hydrobiologia, 2013)

Beguiling and risky: ‘environmental works and measures’ for wetland conservation under a changing climate - Jamie Pittock; C. Max Finlayson; Julia Howitt (Hydrobiologia, 2013)

Insight to Ecosystem Based Approach (EBA) at Landscape Level Using a Geospatial Medium - Nidhi Nagabhatla; Sonali S. Sellamuttu; A. Ghosh Bobba; Max Finlayson; Rohan Wickramasuriya; Martin Van Brakel; S. Narendra Prasad; Chiranjibi Pattanaik (Journal of the Indian Society of Remote Sensing, 2012)

A study of wetland hydrology and ecosystem service provision: GaMampa wetland, South Africa - Matthew McCartney; Sylvie Morardet; Lisa-Maria Rebelo; C. Max Finlayson; Mutsa Masiyandima (Hydrological Sciences Journal, 2011)

The comparative biodiversity of seven globally important wetlands: a synthesis - Wolfgang J. Junk; Mark Brown; Ian C. Campbell; Max Finlayson; Brij Gopal; Lars Ramberg; Barry G. Warner (Aquatic Sciences, 2006)

Biodiversity of the wetlands of the Kakadu Region, northern Australia - C. Max Finlayson; John Lowry; Maria Grazia Bellio; Suthidha Nou; Robert Pidgeon; Dave Walden; Chris Humphrey; Gary Fox (Aquatic Sciences, 2006)